Concepts on Citizenship among University Students and Professors: Coexistence and Social Transformation - Astaíza-Martínez, Andrés Felipe (2019)
A study was conducted among university students and professors during a university course on systematic thought focused on citizenship using a theory grounded methodological approach.  The objective was to identify notions regarding citizenship based on the responses obtained from the students and instructors so that strategies can be developed to transform course dynamics and teaching practices.  Based on the results of this study, participant citizenship is understood as an activity aimed at coexistence and social transformation where is the university serves as a setting for citizen transformation.